2022
DOI: 10.1128/mbio.01822-22
|View full text |Cite
|
Sign up to set email alerts
|

A Bacteriophage-Based, Highly Efficacious, Needle- and Adjuvant-Free, Mucosal COVID-19 Vaccine

Abstract: According to the World Health Organization, COVID-19 may have caused ~15-million deaths across the globe and is still ravaging the world. Another wave of ~100 million infections is predicted in the United States due to the emergence of highly transmissible immune-escaped Omicron variants.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…For instance, some stability tests revealed that T4 was stable for at least ten weeks at room temperature. Therefore, a cold chain is not required to distribute vaccines based on T4 [ 40 ]. Phage DNA vaccines allow gene expression and protein folding in eukaryotic cells, and the eukaryotic expression cassette is protected from degradation [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some stability tests revealed that T4 was stable for at least ten weeks at room temperature. Therefore, a cold chain is not required to distribute vaccines based on T4 [ 40 ]. Phage DNA vaccines allow gene expression and protein folding in eukaryotic cells, and the eukaryotic expression cassette is protected from degradation [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…These mice became protected against a deadly dose of the original SARS-CoV-2 and its Delta variant. Additionally, this vaccine was stable at room temperature and did not affect the microbiome [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phage T4, the best-characterized phage studied to date, belongs to the Straboviridae family [ 6 ] ( (accessed on 1 October 2022)) and infects the Gram-negative Escherichia coli ( E. coli ) and closely related Shigella species [ 33 ]. T4 capsid, a 120 nm long and 86 nm wide prolate icosahedron, encapsidates a ~171 kbp linear, double-stranded DNA genome, and its exterior is decorated with Hoc (highly antigenic outer capsid protein) and Soc (small outer capsid protein) nonessential proteins ( Figure 1 A), which can be fused with foreign proteins for various biomedical applications [ 34 , 35 , 36 , 37 , 38 , 39 ]. T4’s circularly permuted genome consists of ~289 protein coding sequences and encodes 40 structural proteins, with most of them involved in tail assembly ( Figure 1 B) [ 40 , 41 , 42 ].…”
Section: Molecular and Structural Insight Of The Interaction Between ...mentioning
confidence: 99%
“…T4 phage is noninfectious in humans and has demonstrated safety in clinical trials of phage therapy approaches (Sarker et al, 2012(Sarker et al, , 2016(Sarker et al, , 2017. The T4 vectored vaccine is stable for at least 10 weeks at ambient temperature and together with the low cost of phage production offers attractive prospects as a mucosal nanovaccine particularly for developing countries (Zhu, Jain, et al, 2022).…”
Section: Micementioning
confidence: 99%